Active material formulations and preparation methods for LI-S batteries

A sulfur-based material formulation with carbon nanotubes and fibers forms a conductive network to enhance electron transfer and stability, addressing cycling stability issues in Li/S batteries, maintaining capacity over multiple cycles.

JP7604229B2Active Publication Date: 2024-12-23ARKEMA FRANCE SA
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2020543898
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2018-02-19
Filing Date
2019-02-19
Publication Date
2024-12-23
Estimated Expiration
2039-02-19

AI Technical Summary

Technical Problem

Lithium/sulfur (Li/S) batteries suffer from poor cycling stability and rapid capacity decline due to issues such as lithium polysulfides dissolving in the electrolyte, passivation effects, and mechanical stress during discharge, despite the use of carbon-based conductive additives like carbon nanotubes and nanofibers.

Method used

A formulation comprising sulfur-based materials combined with carbon nanotubes and carbon fibers, forming a three-dimensional conductive network to enhance electron transfer and stability, along with a method involving melt-blending and grinding in a liquid phase solvent to ensure uniform dispersion and improved mechanical integrity.

Benefits of technology

The formulation maintains a substantially constant capacity over numerous charge/discharge cycles, improving the cycling stability and charge/discharge capacity of Li/S batteries by ensuring efficient electron transfer and mechanical integrity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007604229000004
    Figure 0007604229000004
  • Figure 0007604229000005
    Figure 0007604229000005
  • Figure 0007604229000001
    Figure 0007604229000001
Patent Text Reader

Abstract

The present invention relates to an active material formulation comprising a sulfur-based material and a conductive composition, wherein the conductive composition comprises carbon nanotubes and carbon fibers. The present invention also relates to a method for preparing the active material formulation, as well as a catholyte containing the formulation, a cathode containing the catholyte, and an accumulator containing the cathode. [Selected Figure] Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the field of lithium / sulfur accumulators, more specifically to an active material formulation for the manufacture of a cathode with improved performance, and also to an accumulator comprising said active material. The present invention also relates to a method for preparing such a formulation. [Background technology]

[0002] The development of rechargeable batteries with high energy density is of great technological and commercial interest. There are many systems, such as portable electronic systems with Li-ion batteries, hybrid vehicles with Ni-MH batteries or other technologies.

[0003] Lithium / sulfur (Li / S) storage batteries, or Li / S batteries, are considered as a promising alternative to Li-ion batteries. The interest in this type of battery arises especially from the high potential energy density of sulfur. In addition, sulfur has the advantages of being abundant, low-cost and non-toxic, which allows the development of large-scale Li / S batteries to be considered.

[0004] The mechanism for discharging and charging a Li / S battery is the reduction / oxidation of sulfur at the cathode (S+2e - ⇔S 2- ) and the oxidation / reduction of lithium at the anode (Li⇔Li + +e - ) In order to allow the electrochemical reactions to occur quickly at the electrodes, the cathode and anode as a whole must be good electronic conductors. However, sulfur discharges relatively slowly and it is an electrical insulator, so it must be made electrically conductive.

[0005] Various improvement approaches aimed at overcoming the low electronic conductivity of sulfur have been considered, in particular the addition of electronically conductive additives such as carbon-based conductive materials.

[0006] The mixing of the active material and the conductive additive can be carried out in various ways. For example, the mixing can be carried out during the preparation of the electrode. In that case, the sulfur is mixed with the conductive additive and possibly the binder by mechanical stirring before the shaping of the electrode. It is believed that this homogenization step distributes the carbon-based additive around the sulfur particles, thereby forming a permeating network. A grinding step can also be used, allowing a more intimate mixing of the materials. However, this additional step may destroy the porosity of the electrode. Another way to mix the active material with the carbon-based additive is to grind the sulfur and the carbon-based additive through a dry method in order to coat the sulfur with carbon. However, when the carbon-based additive is carbon nanotubes, the introduction of carbon nanotubes into the formulation creates some problems. This is because carbon nanotubes have been found to be difficult to handle and disperse due to their small size, being a powder, and sometimes having an entangled structure when obtained by chemical vapor deposition (CVD), as well as generating strong van der Waals interactions between them. The low dispersion of nanotubes limits the effectiveness of charge transfer between the positive electrode and the electrolyte, and therefore limits the performance of Li / S batteries despite the addition of bulk conductive material.

[0007] The applicant has also found that an active material can be obtained by contacting carbon nanotubes (hereinafter referred to as CNTs) with a sulfur-based material in a melting manner, for example in a compounding apparatus, thereby forming an improved active material that can be used in the preparation of an electrode.

[0008] In this case, the sulfur-based material is combined with a carbon-based nanofiller, such as CNT, graphene or carbon black, in a blending tool at the melting point of the sulfur-based material. This allows the production of a sulfur-carbon composite that can be in the form of compact granules. These granules are then ground under an inert atmosphere to obtain a powder that can be used to manufacture the cathode.

[0009] Despite the advantages of Li-S batteries and these new methods that allow for the formation of more uniform active materials, Li-S batteries continue to suffer from a relatively rapid decline in cycling capacity.

[0010] The loss of cycling capacity is multifactorial, including, among others, the formation of some lithium polysulfides during discharge, which dissolve in the electrolyte and escape from the cathode. Capacity loss also occurs through passivation effects and the formation of insoluble sulfides, which are amplified by volumetric fluctuations during discharge, causing mechanical tension and loss of contact with the current collector.

[0011] Numerous methods have been proposed to improve the cycle. For example, the effect of MWNTs (multi-walled nanotubes) and graphite nanofibers (GNFs) on the performance of the cathode of Li-S batteries was studied (Kim Jong-Hwa, et al., Materials Science Forum, 2005, 486-487). MWNTs or GNFs were added as additives to the electrode, which consisted of 60% sulfur, 20% acetylene black, 5% MWNTs or GNFs, and 15% PEO (poly(ethylene) oxide), dissolved in acetonitrile.

[0012] The addition of MWNTs or GNFs results in better electrochemical properties, but the improvement remains limited as after 50 cycles the capacities are only 130 mAh / g for carbon black, 250 mAh / g for carbon black and GNFs, and 300 mAh / g for carbon black and MWNTs, compared to an initial capacity of about 700 mAh / g.

[0013] Solutions based on the combination of nanotubes with other carbon-based fillers, such as carbon black, graphene, or graphene oxide, have also been proposed. For example, Li2S-carbon nanostructured composites obtained by dry ball milling of micron-sized Li2S powder in the presence of carbon black are used together with carbon nanotubes and a simple method of electrochemical activation to improve the use and reversibility of electrodes in the presence of nanotubes.

[0014] Methods involving carbon nanotubes and carbon nanofibers have also been developed with the aim of improving battery performance. However, these methods described in CN106450191 have shown performance retention only at relatively low cycle numbers. The method described in CN107221660, which includes a combination of carbon nanofibers and nanotubes, has shown, in part, that in the presence of carbon nanotubes produces similar results with or without the presence of carbon nanofibers.

[0015] Another method taught in US Patent Publication No. 2011 / 0165462 also discloses the use of carbon nanotubes in combination with carbon nanofibers having a diameter of less than 100 nm for the manufacture of electrodes by winding sheets. These techniques make it possible to resist the formation of dendrites to improve the performance of the battery.

[0016] And carbon nanotubes and carbon nanofibers have been combined to create electrodes that allow sulfur to infiltrate into micropores (<2 nm), thus improving capacity and cycling stability (Linchao Zeng et al. Free-standing porous carbon nanofibers-sulfur composite for flexible Li-S battery cathode, 2014, Vol. 6, 9579-9587).

[0017] Despite the cycling improvements obtained with prior art methods, active material formulations are needed to further improve the cycling stability of Li / S electrodes.

[0018] Additionally, there is a need for active material formulations to increase the charge and discharge capacity of batteries incorporating this active material.

[0019] technical issues The present invention therefore aims to overcome the drawbacks of the prior art, in particular to propose a formulation for producing electrodes with improved cycling stability.

[0020] It is also an object of the present invention to propose a method for the preparation of a formulation for manufacturing an electrode, said method being carried out quickly and simply, and allowing an increase in the charge and discharge capacity of a battery incorporating this active material. Summary of the Invention

[0021] To this end, the present invention relates to an active material formulation comprising a sulfur-based material and a conductive composition comprising carbon nanotubes and at least one other carbon-based filler selected from carbon nanofibers and carbon fibers.

[0022] Preferably, the present invention relates to an active material formulation comprising a sulfur-based material and a conductive composition, characterized in that the conductive composition comprises carbon nanotubes and carbon fibers.

[0023] The performance of the battery can be improved by using the conductive composition according to the present invention. The active materials for Li-S cathodes are generally based on sulfur and carbon. Those produced according to the prior art methods generally have poor cycle stability, especially poor dimensional stability. In particular, the active materials can be damaged during charge and discharge cycles, which results in a decrease in the performance of the battery incorporating said active materials.

[0024] The applicant has therefore developed a novel formulation for improving the performance of batteries, in particular by enabling an improvement in cycling stability. The formulation according to the invention can be used as the cathode active material of a lithium / sulfur accumulator.

[0025] In particular, the applicant has discovered an active material comprising a conductive composition containing at least carbon nanotubes in combination with carbon nanofibers and / or carbon fibers, preferably carbon fibers that can be uniformly dispersed in the bulk of the sulfur-based material and form a three-dimensional nanotube network, which makes it possible to increase the stability and the charge and discharge capacity of a battery incorporating said active material. Unlike carbon black, carbon nanotube type additives also have the advantage of imparting a beneficial adsorption effect to the active material by limiting its dissolution in the electrolyte, thus promoting improved cyclability. Furthermore, the addition of a second aggregate of carbon-based additives, such as carbon fibers, and possibly a third aggregate of carbon-based additives that are coarser than the nanotubes, allows to benefit from the stability synergistic effect of the conductive network in the bulk of the cathode, especially when said cathode is thick (for example greater than 100 μm).

[0026] The advantage of combining the two materials is that the nanofibers, and even the larger diameter carbon fibers, can act as the main conductive path, while the nanotubes act as secondary conductors over short distances where the quality of dispersion is less of an issue.

[0027] According to other optional features of the active material formulation: The conductive composition includes carbon nanotubes, carbon nanofibers and carbon fibers. The best performance is achieved with a combination of these three carbon-based fillers. The conductive composition also comprises another carbon-based filler selected from carbon black, acetylene black, graphite, graphene, activated carbon, and mixtures thereof. The mass ratio of the sulfur-based material to the conductive composition is between 1 / 4 and 50 / 1. The carbon nanotube content is at least 20% by weight of the conductive composition. At least some of the carbon nanofibers, carbon nanotubes and / or carbon fibers are covered with an intrinsically conductive polymer, in particular at least some of the carbon nanotubes and / or carbon fibers are covered with an intrinsically conductive polymer. At least some of the carbon nanofibers, carbon nanotubes and / or carbon fibers are covered with an ion-conducting ceramic material, in particular at least some of the carbon nanotubes and / or carbon fibers are covered with an ion-conducting ceramic material. The sulfur-based material has an S8 content of less than 10% by weight of the sulfur-based material.

[0028] The present invention also relates to a method for preparing an active material formulation according to the present invention, comprising the step of contacting a sulfur-based material with a conductive composition.

[0029] According to another optional feature of the method, the contacting step is selected from: mixing the sulfur-based material with the conductive composition at a temperature equal to or greater than the melting point of the sulfur-based material; sublimating the sulfur-based material onto the conductive composition; liquid-depositing the sulfur-based material onto the conductive composition. The method includes a preliminary step of forming a sulfur-carbon composite, which comprises melting a sulfur-based material and blending the molten sulfur-based material and a carbon-based filler, preferably in a compounding device. The presence of the sulfur-carbon composite in the formulation obtained via the melting method makes it possible to improve the performance of the cathode, since such a composite is more efficient than a sulfur-carbon composite obtained, for example, by co-grinding of sulfur and carbon. The sulfur-carbon composite can be obtained by melting a sulfur-based material and blending the molten sulfur-based material and a carbon-based nanofiller. The method includes a step of grinding the sulfur-carbon composite, the grinding step being optionally performed using a jar mill (cage mill). With horizontal Type and Caged vertical Type), cavitator, jet mill, fluidized bed jet mill, liquid phase mill, screw disperser, brush mill, hammer mill, ball mill, or other pulverization method. - the method comprises the steps of: Introducing the liquid phase solvent and the sulfur-carbon composite into a grinding device, the sulfur-carbon composite comprises at least one sulfur-based material and a carbon-based filler; Implementing a grinding process, - after the grinding step, producing a compound in the form of a solid-liquid dispersion containing the sulfur-carbon composite, and Optionally implementing a drying process. Milling in the presence of a liquid phase solvent allows for improved compound performance compared to dry milling under an inert atmosphere according to prior art methods.

[0030] The present invention also relates to a catholyte comprising an active material formulation and a binder according to the present invention, which is capable of maintaining a substantially constant capacity even after numerous charge / discharge cycles, thus preserving the capacity of a Li-S battery over time.

[0031] According to another optional feature, the catholyte also includes at least one additive selected from a rheology modifier, an ionic conductor, another carbon-based conductor, an electrolyte, and an electron donor component.

[0032] The present invention also relates to the use of the formulation according to the invention for manufacturing a cathode. More specifically, the present invention also relates to a cathode prepared from the active material formulation according to the invention or from the catholyte according to the invention. The active material formulation according to the invention allows improving the electronic conductivity of the electrode formulation, the mechanical integrity of the electrode and therefore the functioning of the battery over time.

[0033] The present invention also relates to a lithium / sulfur accumulator comprising a cathode according to the invention. The active material formulation has a good combination of sulfur donor material and a 3D network of carbon-based fillers, making sulfur accessible to the electrochemical reaction, which may contribute to maintaining good functioning of the battery over time.

[0034] Other advantages and features of the invention will become apparent on reading the following description, given by way of illustrative and non-limiting example with reference to the attached drawings, in which: [Brief description of the drawings]

[0035] [Figure 1] 1 is a schematic representation of a method for preparing an active material formulation according to the present invention, the steps indicated in dashed lines are optional. [Diagram 2] 1 is a schematic diagram of a preferred grinding method according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0036] In the continuation of this specification, the term "active material" refers to a compound capable of ensuring efficient transfer of electricity from the current collector of the electrode and providing an active interface for the electrochemical reaction during the functioning of the battery. More specifically, it corresponds to a compound with which lithium ions can react and from which they can be released. Thus, preferably, in the context of the present invention, the active material corresponds to a sulphur-based material. Thus, for the purposes of the present invention, the term "active material blend" means a mixture of different substances, in particular comprising an active material.

[0037] The term "sulfur-based material" means a sulfur-donating compound selected from natural (or elemental) sulfur, sulfur-based organic compounds or polymers, and sulfur-based inorganic compounds.

[0038] The term "sulfur in elemental form" or "elemental sulfur" refers to sulfur particles in crystalline S8 form or in amorphous form. More specifically, it corresponds to sulfur particles in elemental form that do not contain any sulfur associated with carbon from a carbon-based filler.

[0039] The term "conductive composition" means a composition that includes compounds or structures that are capable of conducting electric current.

[0040] The term "catholyte" means a composition containing components that form a cathode.

[0041] The term "carbon-based filler" may mean a filler comprising at least one element from the group formed by carbon nanotubes, carbon nanofibers, carbon fibers, carbon black, acetylene black, graphite, graphene and activated carbon. The term "filler" usually means a carbon-based filler having a smallest dimension between 0.1 and 20 μm, preferably between 0.1 and 15 μm, more preferably between 0.1 and 10 μm, even more preferably between 0.2 and 10 μm. The term "nanofiller" usually means a carbon-based filler having a smallest dimension measured by light scattering between 0.1 and 200 nm, preferably between 0.1 and 100 nm, more preferably between 0.1 and 50 nm.

[0042] The term "solvent" means a substance that is liquid or supercritical at its operating temperature and that has the property of dissolving, diluting, or extracting other substances without chemical modification or being modified itself. A "liquid phase solvent" is a solvent in liquid form.

[0043] The term "sulfur-carbon composite" refers to an assembly of at least two immiscible components with complementary properties, said immiscible components including a sulfur-based material and a carbon-based filler.

[0044] According to the present invention, the term "compounding equipment" refers to equipment conventionally used in the plastics industry for melt mixing of thermoplastic polymers with additives for the purpose of producing composites, in which the sulfur-based material and the carbon-based filler are mixed by means of a high shear device, such as a co-rotating twin screw extruder or a co-kneader. The molten material generally leaves the equipment in an agglomerated solid physical form, such as in the form of granules.

[0045] For the purposes of the present invention, the term "substantially constant" corresponds to a value that varies by less than 20%, preferably by less than 10%, and even more preferably by less than 5% relative to the value with which it is compared.

[0046] The present invention will now be described in detail and in a non-limiting manner. In the rest of the present document, the same reference numbers are used to denote the same elements.

[0047] As shown in the examples, the inventors have developed a combination of sulfur-based materials and specific conductive compositions that allows for improved cycling capacity and maintenance of dimensional stability.

[0048] Thus, the inventors have developed an active material formulation that can be used to manufacture an electrode, comprising a sulfur-based material and a conductive composition comprising carbon nanotubes and at least one other carbon-based filler selected from carbon nanofibers and carbon fibers. Preferably, the conductive composition comprises carbon nanotubes and carbon fibers. The conductive composition may also comprise carbon nanofibers. As shown in the examples, such a formulation can maintain a virtually constant capacity even after numerous charge / discharge cycles, thus preserving the capacity of a Li-S battery over time.

[0049] The inventors have determined that the conductive composition must include carbon nanotubes in combination with one and / or the other of carbon nanofibers and carbon fibers. Preferably, the conductive composition includes carbon nanotubes and carbon fibers.

[0050] However, they also indicated that preferably the conductive composition comprises carbon nanotubes, carbon nanofibers and carbon fibers. In particular, a combination of at least these three carbon-based fillers gives the best results in terms of maintaining the cycling capacity. In particular, the aggregates of at least two carbon-based fillers in the form of fibrils ensure a better dimensional stability of the cathode with respect to the volume change during charging and discharging.

[0051] The conductive composition comprises 1% to 99% carbon nanotubes and 1% to 99% carbon fibers. In particular, the conductive composition comprises at least 20% carbon nanotubes of single-walled, double-walled, or multi-walled type, preferably at least 30% carbon nanotubes, more preferably at least 40% carbon nanotubes, and even more preferably at least 50% carbon nanotubes.

[0052] In addition, the mass ratio of the sulfur-based material to the conductive composition is preferably between 1 / 4 and 50 / 1. More preferably, the mass ratio of the sulfur-based material to the conductive composition is between 2 / 1 and 20 / 1, and even more preferably between 4 / 1 and 15 / 1.

[0053] According to the invention, the carbon nanotubes may be single-walled carbon nanotubes (SWNTs), double-walled carbon nanotubes (DWNTs) or multi-walled carbon nanotubes (MWNTs); preferably multi-walled. The carbon nanotubes used according to the invention usually have an average diameter of 0.1 to 100 nm, preferably 0.1 to 50 nm, more preferentially 1 to 30 nm or 10 to 15 nm, and advantageously have a length of 0.1 microns or more, advantageously 0.1 to 20 microns, preferably 0.1 to 10 microns.

[0054] The length / diameter ratio, or aspect ratio, of carbon nanotubes is advantageously greater than 10, usually greater than 100. Their specific surface area is, for example, between 50 and 300 m 2 / g, advantageously from 100 to 300m 2 / g, and its apparent density is in particular between 0.01 and 0.5 g / cm 3 between 0.07 and 0.2 g / cm 3 The MWNTs may for example comprise between 5 and 25 layers, and more preferentially between 7 and 20 sheets.

[0055] The carbon nanotubes are in particular obtained by chemical vapor deposition (CVD), for example according to the method described in WO 06 / 082325. Preferably, the carbon nanotubes are obtained from renewable starting materials, in particular of plant origin, as described in patent application EP 1980530.

[0056] An example of carbon nanotubes can be found under the trade name Graphistrength® C100 from Arkema. Such nanotubes may be purified and / or treated (e.g. oxidized) and / or ground and / or functionalized. The grinding of the nanotubes can be carried out by known techniques, under low or high temperature conditions, in equipment such as ball mills, hammer mills, edge runner mills, knife mills or gas jet mills or any other grinding system capable of reducing the size of the entangled network of nanotubes. The grinding is preferably carried out by gas jet grinding techniques, in particular in air jet mills.

[0057] The crude or crushed nanotubes can be purified to free them from possible residual inorganic and metallic impurities, e.g. catalysts resulting from their preparation method, by washing with a sulfuric acid solution. The weight ratio of nanotubes to sulfuric acid can be between 1:2 and 1:3. The purification operation may be further carried out at a temperature ranging from 90° C. to 120° C., for example for 5 to 10 hours. This operation can be advantageously followed by a step of rinsing the purified nanotubes with water and drying.

[0058] Obviously, any other relatively strong acid would be suitable for use. Oxidizing acids such as nitric acid, in addition to removing most of the mineral material, will generate polar surface functions by surface oxidation of the outer layer.

[0059] As a variation, the nanotubes can be purified by a high temperature heat treatment, typically above 1000° C. Alternatively, the carbon nanotubes can be pre-compacted before being subjected to the heat treatment, according to the method described in WO 2018 / 178929.

[0060] The oxidation of the nanotubes is advantageously carried out by contacting them with a sodium hypochlorite solution containing 0.5% to 15% by weight of NaOCl, preferably 1% to 10% by weight of NaOCl, for example with a nanotube:sodium hypochlorite weight ratio ranging from 1:0.1 to 1:1. The oxidation is advantageously carried out at a temperature below 60° C., preferably at room temperature, for a period ranging from a few minutes to 24 hours. This oxidation operation can advantageously be followed by steps of filtering and / or centrifuging, washing and drying the oxidized nanotubes.

[0061] In the present invention, crude, optionally ground, carbon nanotubes are preferably used, i.e. nanotubes that have not been oxidized, purified, functionalized or subjected to other chemical and / or thermal treatments.

[0062] The carbon nanotube content may be between 1% and 99% of the conductive composition. Advantageously, as shown in the examples, the conductive composition contains more than 20% carbon nanotubes, more preferably 40% or more carbon nanotubes. For example, the conductive composition contains between 25% and 75% carbon nanotubes.

[0063] Carbon nanofibers or carbon nanofibrils that may be used in the present invention are also nanofilaments produced by chemical vapor deposition (CVD) from carbon-based sources decomposed with catalysts containing transition metals (Fe, Ni, Co, Cu), such as carbon nanotubes, in the presence of hydrogen at temperatures between 500 and 1200°C. However, these two carbon-based fillers differ in their structure, since carbon nanofibers are composed of somewhat organized graphitic domains (or turbostratic stacks), the planes of which are inclined at variable angles to the axis of the fiber. Such stacks may take the shape of platelets, fish bones or stacked plates to form structures with diameters usually between 50 nm and 500 nm or more. Examples of carbon nanofibers that may be used in particular have diameters between 100 and 200 nm, for example about 150 nm, and advantageously lengths between 5 and 100 microns, preferably between 5 and 75 microns. For example, VGCF nanofibers from Showa Denko KK may be used.

[0064] Thus, the carbon nanofibers contained in the conductive composition preferably have an aspect ratio, ie the ratio between the length and the diameter, of between 10 and 2000.

[0065] Advantageously, as shown in the examples, the conductive composition comprises more than 20% carbon nanofibers, more preferably 40% or more carbon nanofibers, for example, the conductive composition comprises between 25% and 75% carbon nanofibers.

[0066] The carbon fibers that can be used in the present invention are at least partially graphitized, filled or partially porous carbon fibers, preferably having a diameter between 200 nm and 20 μm, preferably between 500 nm and 20 μm, and even more preferably between 500 nm and 8 microns. In the family of carbon fibers, preference is given to ex cellulose or pitch fibers with a small diameter (<5 μm), which is advantageous in avoiding excessive thickness and defects in the electrode structure.

[0067] The carbon fibers contained in the conductive composition preferably have an aspect ratio, ie the ratio between length and diameter, of between 5 and 1000.

[0068] Furthermore, the carbon fibers that may be used in the present invention advantageously have a fiber density of 1.3 to 1.9 g / cm 3 It has a specific gravity between.

[0069] Advantageously, as shown in the examples, the conductive composition comprises more than 20% carbon fibers, more preferably 40% or more carbon fibers. For example, the conductive composition comprises between 25% and 75% carbon fibers. In particular, the conductive composition comprises at least 20% carbon fibers, preferably at least 30% carbon fibers, more preferably 40% carbon fibers.

[0070] More preferably, the conductive composition comprises more than 20% carbon nanotubes and more than 20% of another carbon-based filler selected from carbon nanofibers and carbon fibers. Even more preferably, the conductive composition comprises more than 20% carbon nanotubes, more than 20% carbon nanofibers, and more than 20% carbon fibers.

[0071] The carbon nanotubes, carbon nanofibers and / or carbon fibers may be surface treated to improve their electrical properties. Thus, advantageously, at least a portion of the carbon nanofibers, carbon nanotubes and / or carbon fibers are coated with an intrinsically conductive polymer, such as polyaniline, polythiophene, polypyrrole, etc. Alternatively, at least a portion of the carbon nanofibers, carbon nanotubes and / or carbon fibers are coated with an ionically conductive ceramic material.

[0072] Although good results have been obtained with carbon nanotubes and at least one other carbon-based filler selected from carbon nanofibers and carbon fibers, the active material formulation may also include another carbon-based filler selected from carbon black, acetylene black, graphite, graphene, activated carbon, and mixtures thereof, preferably graphene.

[0073] The term "graphene" refers not only to isolated and individualized flat graphite sheets, but also, by extension, to aggregates containing one to several tens of sheets and having a flat or more or less wavy structure. Such a definition therefore includes FLGs (few-layer graphene), NGPs (nano-sized graphene plates), CNSs (carbon nanosheets) and GNRs (graphene nanoribbons). However, this definition does not include carbon nanotubes and nanofibers, which consist of a coaxial winding of one or more graphene sheets and a turbostratic stack of these sheets, respectively. Furthermore, it is preferred that the graphene used according to the invention is not subjected to additional steps of chemical oxidation or functionalization.

[0074] The graphene used according to the invention is obtained by chemical vapor deposition, i.e. CVD, according to a method using a powdered catalyst, preferably based on mixed oxides. Characteristically, the graphene is in the form of particles having a thickness of less than 50 nm, preferably less than 15 nm, more preferably less than 5 nm, and lateral dimensions of less than 1 micron, preferably between 10 nm and less than 1000 nm, more preferably between 50 and 600 nm, or even between 100 and 400 nm. Each such particle generally contains 1 to 50, preferably between 1 to 20, more preferably between 1 to 10, or even between 1 to 5 sheets, which can be separated from one another in the form of independent sheets, for example during ultrasonic treatment.

[0075] The sulfur-based material may be elemental sulfur, or a sulfur-based molecule, such as a sulfur-based organic compound or polymer, or a sulfur-based inorganic compound, or a mixture thereof in any proportion. Sulfur-based inorganic compounds that may be used as the sulfur-based material include, for example, anionic polysulfides of alkali metals, preferably of the formula Li2S n (n is 1 or more). Preferably, the sulfur-based material comprises elemental sulfur.

[0076] Various sources of natural sulfur are commercially available. The sulfur may be used as is or may be previously purified by different techniques such as smelting, sublimation or precipitation. The sulfur or more generally sulfur-based materials may be subjected to a preparatory step of grinding and / or screening in order to reduce the size of the particles and narrow their distribution. The particle size of the powder may vary within wide limits.

[0077] Sulfur-based inorganic compounds that can be used as sulfur-based materials include, for example, anionic polysulfides of alkali metals, preferably of the formula Li2S n (n≧1).

[0078] The sulfur-based organic compound or polymer may be selected from organic polysulfides, such as organic polythiolates containing functional groups, such as dithioacetals, dithioketals or trithioorthocarbonates, aromatic polysulfides, polyethers, polysulfides, salts of polysulfide acids, thiosulfonates [-S(O)zS-], thiosulfinates [-S(O)-S-], thiocarboxylates [-C(O)-S-], dithiocarboxylates [-RC(S)-S-], thiophosphates, thiophosphonates, thiocarbonates, organometallic polysulfides or mixtures thereof.

[0079] Examples of such organosulfur-based compounds are described inter alia in WO 2013 / 155038.

[0080] According to a particular embodiment of the invention, the sulfur-based material is an aromatic polysulfide.

[0081] The aromatic polysulfide has the following general formula (I): TIFF0007604229000001.tif45170[In the above formula, R1 to R9 may be the same or different and each represents a hydrogen atom, -OH or -O - M + a group or a saturated or unsaturated carbon-based chain containing from 1 to 20 carbon atoms, or -OR 10 represents a group, R10 is an alkyl, arylalkyl, acyl, carboxyalkoxy, alkylether, silyl, or alkylsilyl group, optionally containing 1 to 20 carbon atoms. M represents an alkali metal or an alkaline earth metal; - n and n' are two integers, which may be the same or different, each being equal to or greater than 1 and equal to or less than 8; p is an integer between 0 and 50; - A is a nitrogen atom, a single bond or a saturated or unsaturated carbon-based chain having 1 to 20 carbon atoms. is equivalent to.

[0082] Preferably, in formula (I), R1, R4 and R7 are O - M + It is based on R2, R5 and R8 are hydrogen atoms; R3, R6 and R9 are saturated or unsaturated carbon-based chains containing from 1 to 20 carbon atoms, preferably from 3 to 5 carbon atoms, -The average value of n and n' is about 2, - the average value of p is between 1 and 10, preferably between 3 and 8. (These average values ​​are calculated by the person skilled in the art by assaying for sulfur by weight, based on proton NMR data). -A is a single bond connecting the sulfur atom to the aromatic ring.

[0083] Such poly(alkylphenol) polysulfides of formula (I) are known and can be prepared, for example, in two steps: 1) Reacting sulfur monochloride or sulfur dichloride with an alkylphenol at a temperature of 100 to 200° C. according to the following reaction: In particular, the compound of formula (II) is sold by Arkema under the name Vultac®. 2) O - M +reacting compound (II) with a metal derivative containing the metal M, such as an oxide, hydroxide, alkoxide or dialkylamide of this metal, to obtain a group.

[0084] According to a more preferred variant, R is a tert-butyl or tert-pentyl group.

[0085] According to another preferred variant of the invention, a mixture of compounds of formula (I) is used in which two of the R groups present on each aromatic unit are carbon-based chains containing at least one tertiary carbon via which R is linked to the aromatic nucleus.

[0086] The sulfur-based materials used in the active material formulations according to the present invention may have a variety of heat of fusion values. fus ) is preferably 70 to 100 J.g -1 In particular, the sulfur-based material, for example in elemental or polysulfide form, may be characterized by a heat of fusion, measured during the phase transition (melting) by differential scanning calorimetry (DSC), between 80° C. and 130° C. After the implementation of the preparation method according to the invention, and in particular the incorporation of the carbon-based filler via the melting method, the enthalpy value of the composite (ΔH fus ) decreases.

[0087] Further, preferably, the sulfur-based material has an S8 content of less than 10% by weight of the sulfur-based material. The S8 content can be measured by DSC.

[0088] According to another aspect, the present invention relates to a method for preparing an active material formulation, the method comprising the step of contacting a sulfur-based material with a conductive composition.

[0089] The contacting step according to the present invention can be carried out in many ways. Preferably, the contacting step is selected from: mixing the sulfur-based material with the conductive composition at a temperature equal to or higher than the melting point of the sulfur-based material, subliming the sulfur-based material onto the conductive composition, liquid deposition of the sulfur-based material onto the conductive composition, which is then dissolved in a suitable solvent.

[0090] The present invention provides a method for obtaining an active material formulation having a good combination of sulfur donor material and carbon-based filler particles that facilitates the access of sulfur to the electrochemical reaction, which may contribute to maintaining a good functioning of the battery over time. The active material according to the invention may take the form of a solid-state final product comprising a mixture of particles comprising a conductive composition dispersed in a homogeneous manner in the bulk of a sulfur-based material. In this case, the active material advantageously has a density of 1.4 g / cm3, determined according to NF EN ISO standard 1183-1. 3 The density is usually greater than 2 g / cm 3 Also advantageously, the active material has a porosity of less than 40%, preferably less than 20%. The porosity can be determined based on the difference between the theoretical density and the measured density.

[0091] Preferably, the method for preparing the active material formulation comprises a step of forming a sulfur-carbon composite, the preliminary step of forming said sulfur-carbon composite comprising melting a sulfur-based material and blending the molten sulfur-based material and the carbon-based filler, such a step allowing the formation of a homogeneous mixture.

[0092] However, the melting of the mixture was slower than that of the carbon-based filler (0.05-0.5 g / cm 3 ) and sulfur (2g / cm 3), it is necessary to apply strong mechanical energy to carry out such a mixing, which can be between 0.05 kWh and 1 kWh, preferably between 0.2 and 0.5 kWh per kg of active material. The carbon-based filler is thus homogeneously distributed and is not found only on the surface of the sulfur-based particles. To do this, preferentially compounding equipment is used, i.e. equipment conventionally used in the plastics industry for melt blending of thermoplastics and additives with the aim of producing composites. A method for preparing sulfur-carbon composites via the melt route, which is particularly advantageous in the context of the present invention, is described in WO 2016 / 102865.

[0093] Advantageously, the sulfur-carbon composite is obtained through a manufacturing method comprising the steps of melting a sulfur-based material and blending the molten sulfur-based material with a carbon-based filler. This melting and blending step can advantageously be carried out using a compounding device. Thus, as shown in FIG. 1, the method 100 according to the invention comprises a preliminary step of forming a sulfur-carbon composite, said step of forming the sulfur-carbon composite being: (a) introducing 110 at least one of a sulfur-based material and a carbon-based filler into a compounding apparatus; - optionally, a step 120 of introducing an additive; - carrying out a compounding step 130 to allow melting of the sulfur-based material; and Blending molten sulfur-based material and carbon-based filler 140 Includes.

[0094] To do this, preferably compounding equipment is used, i.e. equipment conventionally used in the plastics industry for the melt mixing of thermoplastic polymers and additives with the aim of producing composites. Thus, the active material according to the invention can be prepared according to a method that also includes recovering 150 the sulfur-carbon composite obtained in the physical form of an agglomerated solid.

[0095] The introducing step 110 is carried out in a compounding device. The sulfur-based material and the carbon-based filler are mixed using a high shear device, such as a co-rotating twin screw extruder or a co-kneader. Typically, the molten material leaves the device in an agglomerated solid physical form, such as in the form of granules, or in the form of rods that are cut into granules after cooling.

[0096] Examples of co-kneaders that can be used are the Buss® MDK 46 co-kneader and the Buss® MKS or MX series co-kneaders sold by BUSS AG, all of which consist of a screw shaft with flights located in a heated barrel, which optionally consists of several parts and whose inner wall is provided with kneading teeth suitable for acting with the flights to shear the material. The shaft is driven in rotation and is given an axial oscillating movement by a motor. These co-kneaders may be equipped with a system for producing granules, for example adapted to the outlet orifice, which system may consist of an extrusion screw or a pump. The co-kneaders that can be used according to the invention preferably have an L / D screw ratio of 7 to 22, for example 10 to 20, and the co-rotating extruders advantageously have an L / D ratio of 15 to 56, for example 20 to 50.

[0097] Preferably, the active material formulation also includes at least one additive selected from a rheology modifier, a binder, an ion conductor, another carbon-based conductor, an electrolyte, an electron donor component, or a combination thereof. Thus, the method may include a step 120 of introducing at least one additive. Like a carbon-based filler, the additive may be incorporated into the active material formulation via a melt process, for example, during step 120.

[0098] These additives are advantageously introduced before or during the compounding step in order to obtain a homogeneous active material formulation, in which in this embodiment the sulfur-based material and the conductive composition then represent 50% to 99% by weight, preferably 60% to 95% by weight, based on the total weight of the active material formulation.

[0099] In particular, in order to reduce self-heating of the mixture in the compounding equipment, it is possible to add rheology modifiers, i.e. additives that reduce the rheology of the sulfur in the molten state, during mixing, before or during the compounding step. Such additives are described in WO 2013 / 178930. Examples include dimethyl sulfide, diethyl sulfide, dipropyl sulfide, dibutyl sulfide, their trisulfide homologues, their tetrasulfide homologues, their pentasulfide homologues, their hexasulfide homologues, alone or in any proportion of two or more of them.

[0100] The amount of the rheology modifying additive is typically from 0.01 to 5% by weight, preferably from 0.1 to 3% by weight, based on the total weight of the active material formulation.

[0101] The active material formulation may contain binders, in particular polymeric binders. The polymeric binders may also provide dimensional plasticity or flexibility to the electrodes formed from the active materials. Advantageously, these binders are introduced before or during the formulation process. Moreover, an important role of the binder is also to ensure a uniform dispersion of the active material and, for example, the sulfur-carbon composite particles. Various polymeric binders may be used in the formulation according to the invention, which may be selected, for example, from halogenated polymers, preferably fluoropolymers, functionalized polyolefins, polyacrylonitriles, polyurethanes, polyacrylic acids and their derivatives, polyvinyl alcohols and polyethers, and mixtures thereof in all proportions.

[0102] Examples of fluoropolymers that may be mentioned include poly(vinylidene fluoride) (PVDF), preferably in alpha form, poly(trifluoroethylene) (PVF3), polytetrafluoroethylene (PTFE), copolymers of vinylidene fluoride and 1-hexafluoropropylene (HFP) or trifluoroethylene (VF3) or tetrafluoroethylene (TFE) or chlorotrifluoroethylene (CTFE), fluoroethylene / propylene (FEP) copolymers, copolymers of ethylene and fluoroethylene / propylene (FEP) or tetrafluoroethylene (TFE) or chlorotrifluoroethylene (CTFE), perfluoropropyl vinyl ether (PPVE), perfluoroethyl vinyl ether (PEVE), 2,3,3,3-tetrafluoropropene, and copolymers of ethylene and perfluoromethyl vinyl ether (PMVE), or mixtures thereof.

[0103] Examples of polyethers that may be mentioned include poly(alkylene oxides), such as poly(ethylene oxide) PEO, polyalkylene glycols, such as polyethylene glycol PEG, polypropylene glycol PPG, polytetramethylene glycol (PTMG), polytetramethylene ether glycol (PTMEG), and the like.

[0104] The polymer binder may also be selected from block copolymers of these polymers, such as copolymers containing PEO / PPO / PEO blocks. More preferably, the polymer binder is PVDF or PEO. POE may be used in acetonitrile or isopropanol, as may PTFE suspended in ethanol or water. The most common polymer is still poly(vinylidene fluoride) (PVDF), used in solution in N-methyl-2-pyrrolidone (NMP). This polymer is not only chemically stable with respect to organic electrolytes, but also electrochemically stable in the potential window of Li / S accumulators. It is insoluble in organic solvents and barely swells, allowing the electrode to retain its morphology and mechanical strength during cycling.

[0105] Possible binders are also from the polysaccharide family, such as carboxymethylcellulose (CMC), hydroxyethylcellulose (HEC), etc. Preferably, the binder is PVDF, PEO or CMC.

[0106] The amount of binder is generally about 20% by weight of the active material formulation, preferably between 5% and 15% by weight.

[0107] The active material formulation may include an ionic conductor that has a favorable interaction with the surface of sulfur or sulfur-based molecules to enhance the ionic conductivity of the active material. Examples of ionic conductors that may be included include, but are not limited to, lithium organic salts, such as lithium imidazolate salts. Also included are poly(alkylene oxides), which, apart from their role as binders, may provide ionic conductive properties to the active material.

[0108] The active material formulation may also contain another conductor, advantageously a carbon-based conductor such as carbon black, graphite or graphene, in a proportion that may generally range from 1% to 10% relative to the sulfur-based molecules. Preferably, carbon black is used as the conductor. The active material formulation may also contain an electron donor component to improve the electron exchange during charging and to control the length of the polysulfides, optimizing the charge / discharge cycle of the battery. Advantageously, as the electron donor component, a component from groups IVa, Va and VIa of the periodic table, preferably selected from Se, Te, Ge, Sn, Sb, Bi, Pb, Si or As, in powder form or salt form, is used.

[0109] These compounds may generally be added in proportions that may range from 1% to 10% by weight relative to the weight of the sulfur-based material.

[0110] The active material formulation is preferably made of lithium (bis)trifluoromethanesulfonate imide (LiTFSI), lithium 2-trifluoromethyl-4,5-dicyanoimidazole (LiTDI), lithium bis(fluorosulfonyl)imide (LiFSI), lithium hexafluorophosphate (LiPF6), lithium perchlorate (LiClO4), lithium trifluoromethylsulfonate (CF3SO3Li), lithium trifluoroacetate (CF3COOLi), lithium dodecafluorododecaborate (Li2B 12 F 12 ), lithium bis(oxalato)borate (LiBC4O8), and lithium tetrafluoroborate (LiBF4). More preferably, the electrolyte liquid solvent comprises LiTFSI.

[0111] The compounding step 130 is carried out at a temperature above the melting point of the sulfur-based material. In the case of elemental sulfur, the compounding temperature can range from 120° C. to 150° C. In the case of other types of sulfur-based materials, the compounding temperature is clearly determined by the material used, whose melting point is generally given by the material supplier. The residence time is also adapted to the properties of the sulfur-based material.

[0112] This method allows for efficient and uniform dispersion of large amounts of carbon-based filler in the sulfur-based material, regardless of density differences between compositions of the active material blend.

[0113] In order to achieve optimal dispersion of the carbon-based filler in the sulfur-based material in the compounding apparatus, a large mechanical energy input is required, preferably greater than 0.05 kWh per kg of material.

[0114] When compounding is carried out in an extruder, the active material blend is advantageously obtained in the form of extrudates whose diameter may range from 0.5 to 5 mm.

[0115] The method may also include blending 140 the molten sulfur-based material with the carbon-based filler. The blending may be carried out in any kneading, blending or extrusion equipment known to those skilled in the art and compatible with the active material formulation, particularly at the temperatures during the compounding process.

[0116] The mixture of particles is then milled during a milling step 160 to obtain a powder that does not contain any particles with a size greater than 100 microns, preferably does not contain particles with a size greater than 25 microns, which facilitates the electrode manufacturing process. The carbon-based filler is mixed with sulfur-based molecules, particularly sulfur, preferably via a melting method. The milling step can be carried out in the solid state, that is to say in dry form.

[0117] The process of crushing the sulfur-carbon composite is carried out using a jar mill (cage mill). With horizontal Type and Caged vertical Type ), cavitator, jet mill, fluidized bed jet mill, liquid phase mill, screw disperser, brush mill, hammer mill, ball mill, or other method for pulverizing solid materials.

[0118] Furthermore, the inventors have developed a method for preparing a formulation for the manufacture of electrodes from sulfur-carbon composites that can improve the charge and discharge capacity and improve the interface, for example by performing the grinding in a liquid-phase solvent containing an electrolyte salt and / or a solid electrolyte. As will be described in detail below, the production of a favorable interface from the grinding process allows for the improvement of the performance of the active material formulation. More specifically, grinding in the presence of the electrolyte allows for the direct production of catholyte, which can then be used to form a cathode.

[0119] As shown in FIG. 2, the improved grinding method according to the present invention includes: - introducing a liquid phase solvent into the grinding device 210; - introducing 220 the sulfur-carbon composite into a grinding device, the sulfur-carbon composite comprising at least one sulfur-based material and a carbon-based filler; - a step 230 for carrying out a grinding step, - a step 240 of producing, after said grinding step, an active material formulation in the form of a solid-liquid dispersion, comprising sulfur-carbon composites in the form of particles having a median diameter D50 of less than 50 μm; Includes.

[0120] Steps 210 and 220 prior to grinding step 230 are shown in a particular order in Figure 2. However, in accordance with the present invention, the order in which materials are introduced into the mill may be modified without this being considered a separate invention.

[0121] As shown in FIG. 2, the method according to the present invention includes a step 210 of introducing a liquid phase solvent into a milling apparatus.

[0122] Preferably, the amount of solvent used allows the formation of a solid-liquid dispersion having a solids weight content of less than 90%, preferably less than 80%, more preferably between 30% and 60%.

[0123] The solvent used during the milling step may be a solvent that can be evaporated before the production of the electrode. In this case, the solvent is preferably selected from liquid phase solvents having a boiling point below 300° C., preferably below 200° C., more preferably below 115° C., even more preferably below 100° C. Thus, the solvent can be evaporated after the milling step without resulting in modification of the carbon-sulfur composite.

[0124] In this regard, the liquid phase solvent used in the present invention may, for example, comprise at least one protic or aprotic solvent, said protic or aprotic solvent being selected from water, alcohols, ethers, esters, lactones, N-methyl-2-pyrrolidone and dimethylsulfoxide.

[0125] Alternatively, the liquid phase solvent used is water or alcohol, and the solvent is removed by a freeze-drying process.

[0126] Additionally, the liquid phase solvent is preferably degassed prior to being introduced into the milling apparatus.

[0127] As shown in FIG. 2, the method according to the present invention includes a step 220 of introducing the sulfur-carbon composite into a grinding device.

[0128] The sulfur-carbon composite comprises at least one sulfur-based material and a carbon-based filler.

[0129] The sulfur-carbon composite may be in the form of a solid or solid material having a median diameter D50 of more than 50 μm before the grinding step.

[0130] The sulfur-carbon composites used during the grinding process can be obtained through several methods and have shapes and dimensions defined by their manufacturing method. Advantageously, the sulfur-carbon composites are obtained through a manufacturing method that includes melting a sulfur-based material and blending the molten sulfur-based material with a carbon-based filler, preferably in the presence of strong mechanical energy. This melting and blending step can advantageously be carried out using a compounding device. The sulfur-carbon composites are generally in an agglomerated physical form, for example in the form of granules. In this case, the granules' morphology will depend on the diameter of the holes of the die and the speed of the knife. The granules can have at least one dimension, for example, between 0.5 mm and several millimeters.

[0131] Thus, preferably, the sulfur-carbon composite is in the form of a solid, such as a granule or particle, having a median diameter D50 of more than 100 μm, preferably more than 200 μm, more preferably more than 500 μm.

[0132] The sulfur-carbon composites advantageously used in connection with the present invention comprise a carbon-based filler infiltrated in a molten sulfur-based matrix, the carbon-based filler being uniformly distributed throughout the body of the sulfur-based material, which can be visualized, for example, by electron microscopy. The sulfur-based material / carbon-based filler mixture has a morphology suitable for optimizing the functionality of Li / S battery electrodes. Thus, the carbon-based filler is uniformly distributed throughout the body of the particle and is not found only on the surface of the sulfur-based particle.

[0133] The active material according to the invention, i.e. based on this sulfur–carbon composite, can thus provide an efficient transfer of electricity from the current collector of the electrode and provide an active interface for the electrochemical reactions during battery function.

[0134] As shown in FIG. 2, the method according to the present invention includes a grinding step 230 .

[0135] Grinding in the liquid state has the advantage of not introducing excessive porosity into the resulting active material, so that the resulting powder has a higher density than powders obtained via conventional methods.

[0136] The grinding process is carried out using a cage mill. With horizontal Type and Caged vertical Type ), cavitator, jet mill, fluidized bed jet mill, liquid phase mill, screw disperser, brush mill, hammer mill, ball mill, or other method for pulverizing solid materials.

[0137] The grinding step is generally carried out for at least 30 minutes. Preferably, the grinding step is carried out for at least 1 hour, more preferably at least 2 hours.

[0138] Advantageously, the method according to the invention may comprise two successive grinding steps carried out in two different grinding devices.

[0139] The grinding step is generally carried out at a temperature below the boiling point of the liquid phase solvent. Advantageously, the grinding step is carried out at a temperature below the melting point of the sulfur-based material. The grinding step is preferably carried out at a temperature below 300°C, more preferably below 200°C, even more preferably at a temperature below 110°C.

[0140] Moreover, contrary to the prior art methods, the grinding step is preferably carried out at a temperature above 0° C. More preferably, the grinding step is carried out at a temperature above 10° C.

[0141] Thus, the grinding step is carried out at a temperature between 1° C. and 300° C., preferably between 5° C. and 200° C., more preferably between 5° C. and 110° C. It is to be understood that when the term “between” is used, the limits are included. The grinding step will likely generate heating of the mixture caused by friction caused by the grinding step. Thus, self-heating is allowed to reach the desired temperature, after which the method may include a step of cooling the mixture so as to remain below the boiling point of the liquid phase solvent used in particular.

[0142] If this is required, via the liquid route, the grinding step may be followed by a step of mixing the solid-liquid dispersion with additives which may be other components of the electrode.

[0143] As shown in Figure 2, the method according to the invention comprises a step 240 of obtaining a formulation in the form of a solid-liquid dispersion produced during a grinding step. Moreover, this formulation comprises sulfur-carbon composites in the form of particles having a median diameter D50 of less than 50 μm, less than 10% by number of the particles of the dispersion being particles of sulfur in elemental form.

[0144] The formulations in the form of solid-liquid dispersions defined by the present invention can increase the specific capacity of the electrode and enhance the charge and discharge capacity of the electrode, thus providing an efficient transfer of electricity from the current collector of the electrode and providing an active interface for the electrochemical reactions during the functioning of the battery.

[0145] As shown in Figure 2, the method according to the invention comprises a drying step 250. The drying step 250 allows the production of an active material formulation in the form of a powder. The active material formulation obtained from the solid-liquid dispersion then advantageously has a water content of less than 100 ppm.

[0146] This drying step can be carried out, for example, via a spraying process. This active material powder has the same advantages as the blend, i.e. improved performance due to low content of elemental sulfur and / or low oxidation. This powder is then blended with the additives and used in a dry manner.

[0147] The active material formulation in powder form according to the invention comprises particles exhibiting a homogeneous mixture of carbon-based filler dispersed in a homogeneous manner in a body of sulfur-based material. The active material formulation advantageously has a powder density of 1.6 g / cm3, as determined according to NF EN ISO standard 1183-1. 3 It has a density greater than

[0148] The active material formulation also advantageously has a porosity of less than 20%, which can be determined from the difference between the theoretical density and the measured density. Preferably in powder form as previously characterized, the active material formulation advantageously has a porosity of less than 20% and / or a density of less than 1.6 g / cm 3 The active material formulations according to the invention, having a density of greater than 100%, can be used to prepare electrodes, particularly cathodes, of Li / S batteries. The active material generally comprises about 20% to 95% by weight, preferably 35% to 80% by weight, of the total electrode formulation.

[0149] Moreover, the heat of fusion of the sulfur-based material in the sulfur-carbon composite forming the active material according to the invention is lower than the heat of fusion of the sulfur-based material found in the formulation or active material formed by the methods of the prior art. Thus, preferably, the sulfur-based material of the sulfur-carbon composite has a heat of fusion that is at least 10%, more preferably at least 15%, more preferably at least 20% less than the heat of fusion of the sulfur-based material used to form the sulfur-carbon composite, as measured by differential scanning calorimetry (e.g., under nitrogen flow at 5°C / min) between 80°C and 130°C. It does not depart from the scope of the present invention if the sulfur-carbon composite does not have the heat of fusion of the sulfur-based material between 80°C and 130°C, i.e. is amorphous.

[0150] Advantageously, the sulfur-based material of the sulfur-carbon composite has a thermal conductivity of 60 J.g as measured by differential scanning calorimetry between 80° C. and 130° C. (e.g., under nitrogen flow at 5° C. / min). -1 Less than 55 J.g -1 less than 50 J.g -1 It has a heat of fusion of less than 1000 nm.

[0151] According to another aspect, the present invention relates to a catholyte comprising an active material formulation according to the present invention and a binder.

[0152] Preferably, the binder is selected from, in particular, acrylic polymers, methacrylic polymers, fluoropolymers, polyethers, polyesters, polysaccharides such as cellulose and derivatives thereof, in particular CMC, functionalized polyolefins, polyethyleneimines, polyacrylonitriles, polyurethanes, polyvinyl alcohols, polyvinylpyrrolidones, copolymers thereof, and mixtures thereof.

[0153] The catholyte also contains at least one additive selected from a rheology modifier conductor, another carbon-based conductor, an electrolyte, and an electron donor component. The catholyte may contain one or more of each of these additives. These additives have already been described above; thus, the catholyte according to the invention may contain the additives mentioned above, in particular the preferred additives.

[0154] The electrolyte is preferably selected from LiNO2, LiFSI, LiTFSI, LiTDI and other Li salts, and mixtures thereof. More preferably, the electrolyte comprises LiFSI, LiTFSI and / or LiTDI. Furthermore, at least a portion of the electrolyte may be an ionically conducting ceramic or solid electrolyte.

[0155] The carbon-based conductor is preferably selected from carbon black, acetylene black, graphite, graphene, carbon nanofibers, carbon fibers, activated carbon, intrinsically conductive polymers, and mixtures thereof. In particular, in the active material formulation according to the invention, fibers and / or nanofibers, preferably carbon fibers, are present, with the possibility of adding such fibers or nanofibers again to the catholyte.

[0156] Furthermore, the catholyte according to the invention may comprise a liquid solvent, also called electrolyte liquid solvent, capable of dissolving at least one electrolyte salt. The electrolyte liquid solvent may be selected, for example, from monomers, oligomers, polymers, and mixtures thereof. In particular, the liquid phase solvent comprises at least one compound selected from water, amides, carbonates, ethers, sulfones, fluoro compounds, toluene, and dimethyl sulfoxide. The amide is preferably N-methyl-2-pyrrolidone (NMP) or N,N-dimethylformamide (DMF).

[0157] The electrolyte liquid solvent is preferably a solvent suitable for lithium-sulfur batteries; in this case, no evaporation step needs to be performed after the grinding step, allowing direct compounding of the cathode. Thus, preferably, the liquid phase solvent comprises at least one compound selected from carbonates, ethers, sulfones, fluoro compounds, and toluene.

[0158] Carbonate esters can be used as electrolyte liquid solvents: ethers in particular make it possible to obtain good dissolution of lithium polysulfides and generally have lower dielectric constants than those of carbonates, but ether type solvents offer relatively high ionic conductivity and the ability to solvate lithium ions.

[0159] Thus, preferably, the electrolyte liquid solvent is an ether such as 1,3-dioxolane (DIOX) or 1,2-dimethoxyethane (DME), or a carbonate ester such as dimethyl carbonate (DMC) or propylene carbonate (PC).

[0160] The electrolyte liquid solvent may also include a combination of solvents. For example, the electrolyte liquid solvent may include an ether and a carbonate. This may allow for a reduction in the viscosity of the mixture including the polymeric carbonate.

[0161] Preferably, the electrolyte liquid solvent is selected from the following: 1,3-dioxolane (DIOX), 1,2-dimethoxymethane (DME), ethylene carbonate (EC), diethyl carbonate (DEC), propylene carbonate (PC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), methyl propyl carbonate, tetrahydrofuran (THF), 2-methyltetrahydrofuran, methyl propyl propionate, ethyl propyl propionate, methyl acetate, diglyme (2-methoxyethyl ether), tetraglyme, diethylene glycol dimethyl ether (diglyme, DEGDME), polyethylene glycol dimethyl ether (PEGDME), tetraethylene glycol dimethyl ether (TEGDME), ethylene carbonate, propylene carbonate, butyrolactone, dioxolane, hexamethylphosphoamide, pyridine, dimethyl sulfoxide, tributyl phosphate, trimethyl phosphate, N-tetraethylsulfamide, sulfone, and mixtures thereof.

[0162] More preferably, the electrolyte liquid solvent is selected from the following: tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, methyl propyl propionate, ethyl propyl propionate, methyl acetate, dimethoxyethadiglyme (2-methoxyethyl ether), tetraglyme, ethylene carbonate, propylene carbonate, butyrolactone, dioxolane, hexamethylphosphoamide, pyridine, dimethyl sulfoxide, tributyl phosphate, trimethyl phosphate, N-tetraethylsulfamide, sulfone, and mixtures thereof.

[0163] Other solvents such as sulfones, fluoro compounds or toluene may also be used.

[0164] Preferably, the solvent is a sulfone or a mixture of sulfones, examples of sulfones are dimethylsulfone and sulfolane. Sulfolane can be used as the sole solvent or in combination with, for example, other sulfones. In one embodiment, the electrolyte liquid solvent includes lithium trifluoromethanesulfonate and sulfolane.

[0165] The present invention also relates to the use of said active material formulation in an electrode, in particular in a Li / S battery cathode. The active material according to the invention makes it possible to improve the electronic conductivity of the electrode formulation, the mechanical integrity of the electrode and therefore the functioning of the battery over time.

[0166] Thus, according to another aspect, the present invention relates to the use of a formulation according to the invention for the manufacture of an electrode, in particular a cathode.

[0167] To do this, the formulation in the form of a particulate mixture can be deposited on a current collector.

[0168] The active material formulation can be applied to a current collector in the form of a suspension in a solvent (e.g., water or an organic solvent). The solvent can then be removed, for example by drying, and the resulting structure can be blocked to form a composite structure, which can be cut to the desired shape to form the cathode.

[0169] In one embodiment, the cathode comprises 1% to 5% by weight of PEO and 1% to 5% by weight of a binder selected from gelatin, cellulose (e.g., carboxymethylcellulose) and / or rubber (e.g., styrene-butadiene rubber). Such binders can improve the life of the battery. The use of such binders can also allow the total amount of binder to be reduced, for example, to a level of 10% by weight or less of the total weight of the cathode.

[0170] The cathodes described herein can be used in lithium-sulfur batteries.

[0171] According to another aspect, the present invention provides a lithium / sulfur accumulator or a lithium-sulfur battery comprising the cathode described above.

[0172] The lithium / sulfur accumulator may also include an anode that includes an alloy of lithium metal or an alloy of lithium metal and an electrolyte.

[0173] The electrolyte may be a solid electrolyte or may include at least one lithium salt and at least one organic solvent.

[0174] In some cases, a separator may be placed between the cathode and the anode. For example, during assembly of the battery, the separator may be placed on the cathode and the lithium negative electrode on the separator. The electrolyte is then introduced into the assembled battery to wet the cathode and the separator. As a variation, the electrolyte may be applied to the separator, for example by coating or spraying, before the lithium negative electrode is placed on the separator. The separator is usually composed of a porous membrane of polyolefin (polyethylene, polypropylene). This component is only used in combination with a liquid electrolyte, since the polymer electrolyte or gelled electrolyte already ensures the physical separation of the electrodes by itself. When a separator is present in the battery of the invention, the separator may comprise any suitable porous membrane or substrate that allows ions to move between the electrodes of the battery. To prevent direct contact between the electrodes, the separator must be placed between the electrodes. The porosity of the substrate must be at least 30%, preferably more than 50%, for example more than 60%. Suitable separators include lattices formed from polymeric materials. Suitable polymers include polypropylene, nylon and polyethylene. Non-woven polypropylene is particularly preferred. It is also possible to use multi-layer separators. The separator may include a carbon-based filler. The separator may be Li-Nafion.

[0175] As explained above, the battery includes an electrolyte. The electrolyte is present or disposed between the electrodes, allowing charge to be transferred between the anode and the cathode. Preferably, the electrolyte wets the cathode pores and also the pores of, for example, the separator. Organic solvents that can be used in the electrolyte are those described above as electrolyte liquid solvents.

[0176] The following examples illustrate the invention but do not have any limiting nature. EXAMPLES

[0177] Example 1: Preparation of S / nanotube active material blend Nanotubes (Graphistrength® C100 from Arkema) and solid sulfur (50-800 microns) were introduced into the first feed hopper of a Buss® 25 MDK 46 co-kneader (L / D=11) equipped with an electric discharge extrusion screw and a granulation device.

[0178] The nominal temperature values ​​in the co-kneader were: Zone 1: 140°C; Zone 2: 130°C; Screw: 120°C. At the exit of the die, a mixture consisting of 87.5% by weight of sulfur and 12.5% ​​by weight of nanotubes is in the form of granules obtained by pelletizing and is cooled by air.

[0179] Example 2 Graphistrength® C100 nanotubes from Arkema (diameter 15 nm, length 1-10 nm, apparent density 0.08), VGCF H nanofibers from Showa Denko K.K. (diameter 150 nm, length 10-20 microns, apparent density 0.08), and solid sulfur (50-800 microns) were introduced into the first feed hopper of a Buss® 25 MDK 46 co-kneader (L / D=11) equipped with an electric discharge extrusion screw and a granulator.

[0180] The nominal temperature values ​​in the co-kneader were: Zone 1: 140°C; Zone 2: 130°C; Screw: 120°C. At the exit of the die, a mixture consisting of 87.5% by weight of sulfur, 10% by weight of nanotubes and 2.5% by weight of nanofibers is in the form of granules obtained by pelletizing and cooled by air.

[0181] Example 3 The fibers chopped to 5 mm, obtained by carbonizing Arkema Graphistrength® C100 carbon nanotubes (diameter 15 nm, length 1-10 nm, apparent density 0.08) sulfur and viscose fibers under N2 at between 180 and 1200 °C with a residence time of 15 min, were introduced into the first feed hopper of a Buss® 25 MDK 46 co-kneader (L / D=11) equipped with an electric discharge extrusion screw and a granulator. The specific gravity of the fibers is 1.45 and their diameter is between 1 and 5 μm. At the exit of the die, a mixture consisting of 87.5% by weight of sulfur, 10% by weight of nanotubes and 2.5% by weight of ex viscose fibers is in the form of granules obtained by pelletizing and cooled with air.

[0182] Example 4 Example 2 is repeated, but using a conductor consisting of 60% Graphistrength® C100 nanotubes and 40% VGCF H nanofibers, other parameters remain unchanged.

[0183] Example 5 Example 2 is repeated, but using a conductor consisting of 40% Graphistrength® C100 nanotubes and 60% VGCF H nanofibers, other parameters remain unchanged.

[0184] Example 6 Example 2 is repeated, but using a conductor consisting of 20% Graphistrength® C100 nanotubes and 80% VGCF H nanofibers, other parameters remain unchanged.

[0185] Example 7 Example 2 is repeated, but using a conductor made of 100% VGCF H nanofibers, other parameters remain unchanged.

[0186] Example 8 A composite is prepared with a conductor content equal to 20% (12% nanotubes and 8% nanofibers) and a sulfur content equal to 80%, the other parameters remaining unchanged.

[0187] Example 9 A composite is prepared with a conductor content equal to 20% (12% nanotubes and 8% ex viscose carbon fibers) and a sulfur content equal to 80%, the other parameters remaining unchanged.

[0188] Example 10 A composite is prepared with a composition of 87.5% sulfur, 7.5% nanotubes, and 5% nanofibers.

[0189] Example 11 A formulation is prepared with 80% sulfur, 10% carbon nanotubes, 5% VGCF H nanofibers and 5% ex viscose carbon fibers.

[0190] Example 12: Evaluation of active material formulations Tests were performed on a Li / S battery model containing: 1) Anode made from Li metal, 100 microns thick 2) Separator / membrane (20 microns) 3) Sulfolane-based electrolyte containing 1M Li+ 4) A cathode based on a sulfur-based formulation supported by a collector made of Al.

[0191] The following benchmark cathode formulations were tested: A reference formulation, representative of the prior art, containing 70% by weight of sulfur, 10% by weight of carbon black, and 20% by weight of PEO (Polyox WSR N-60K) [Comparative Example 1] - A formulation containing 80% by weight of the active material of Example 1, 5% by weight of carbon black and 15% by weight of PEO [Comparative Example 2] - Reference formulation containing 70% by weight of sulfur, 15% by weight of carbon nanotubes and 15% by weight of PEO [Comparative Example 3]

[0192] The other formulations are represented as 100% sulfur and conductive additive plus 15% PEO.

[0193] The cathode formulation was applied to the electrode via a paste in a solvent, then dried and pressed.

[0194] The capacity of the cathode of the test cell is 1.5 to 3 Ah / cm 2 The test cells were subjected to charge / discharge conditions. The performance of the cathode was evaluated after 150 cycles and is reported in the following table. TIFF0007604229000003.tif138170

[0195] These results confirm that the active material according to the invention comprising a carbon-based filler is able to improve the service life and therefore the efficiency of Li / S batteries, especially when a specific ratio between nanotubes and nanofibers is applied.

[0196] Moreover, as can be seen by comparing the cycle stability of the compositions according to Examples 2 and 4, when the conductive composition contains more than 20% carbon nanofibers, more preferably 40% or more carbon nanofibers, the stability is further substantially improved. Moreover, in the presence of carbon fibers, the performance is also improved, as demonstrated by Examples 3 and 9. In particular, the presence of carbon fibers makes it possible to ensure a performance after 150 cycles that is significantly better than the composition containing only CNTs. And the cycle stability is improved when the conductive composition contains at least 20% carbon fibers, and is even more improved when the conductive composition contains at least 40% carbon fibers.

[0197] Similarly, as can be seen by comparing the cycling stability of the compositions according to Examples 4 and 6, when the conductive composition contains more than 20% carbon nanotubes, more preferably 40% or more carbon nanotubes, the stability is further substantially improved.

[0198] As illustrated in Examples 4, 5 and 6, the decrease in the amount of nanotubes in favor of the increase in carbon nanofibers reduces the performance after 150 cycles. According to Examples 2 and 6, the performance is the same independently of the amount of carbon nanotubes relative to the amount of carbon nanofibers, but in the presence of carbon nanotubes and carbon fibers, the performance is improved even after 150 cycles. Moreover, for Examples 3 and 9, the performance is improved when the amount of carbon nanotubes and carbon fibers increases. Thus, in the presence of carbon fibers and carbon nanotubes, the performance is particularly improved when the composition contains more than 20% carbon fibers.

[0199] And the combination of carbon nanotubes, carbon nanofibers and carbon fibers (Example 11) gives the best results, especially when the conductive composition contains 25% or more carbon nanofibers and 25% or more carbon fibers.

Claims

1. 1. An active material formulation comprising a sulfur-based material and a conductive composition, the conductive composition comprising carbon nanotubes, carbon fibers, and carbon nanofibers, the carbon fibers having a diameter between 200 nm and 20 μm, and the carbon nanofibers having an aspect ratio between 10 and 2000.

2. 10. The active material formulation of claim 1, wherein the conductive composition also includes another carbon-based filler selected from carbon black, acetylene black, graphite, graphene, activated carbon, and mixtures thereof.

3. 3. The active material formulation of claim 1 or 2, wherein the mass ratio of the sulfur-based material to the conductive composition is between 1 / 4 and 50 / 1.

4. 4. The active material formulation of claim 1, wherein the carbon nanotube content is at least 20% by weight of the conductive composition.

5. 5. The active material formulation of claim 1, wherein at least a portion of the carbon nanofibers, carbon nanotubes and / or carbon fibers are coated with a conductive polymer.

6. 6. The active material formulation of claim 1, wherein the sulfur-based material has an S8 content of less than 10% by weight of the sulfur-based material.

7. A catholyte comprising the active material formulation of any one of claims 1 to 6 and a binder.

8. 8. The catholyte of claim 7, further comprising at least one additive selected from a rheology modifier, an ion conductor, another carbon-based conductor, an electrolyte, and an electron donor component.

9. 7. A method for preparing the active material formulation of claim 1, comprising the step of contacting a sulfur-based material with a conductive composition.

10. 10. The method of claim 9, wherein the contacting step is selected from the group consisting of: mixing the sulfur-based material with the conductive composition at a temperature equal to or higher than the melting point of the sulfur-based material; sublimating the sulfur-based material on the conductive composition; and liquid-depositing the sulfur-based material onto the conductive composition.

11. 10. The method according to claim 9, further comprising a step of forming a sulfur-carbon composite, characterized in that the preliminary step of forming the sulfur-carbon composite comprises melting a sulfur-based material and blending the molten sulfur-based material and a carbon-based filler, preferably in a compounding apparatus.

12. A preparation method according to any one of claims 9 to 11, characterized in that it comprises a step of grinding the sulfur-carbon composite.

13. The following steps: - introducing a liquid phase solvent and a sulfur-carbon composite into a grinding device (210), (220), wherein the sulfur-carbon composite comprises at least one sulfur-based material and a carbon-based filler; - implementing a grinding process (230); - producing (240) a compound in the form of a solid-liquid dispersion comprising the sulfur-carbon composite after said grinding step, - Optionally implementing a drying step (250) 13. A process according to any one of claims 9 to 12, characterized in that it comprises:

14. A cathode prepared from the catholyte of claim 7 or 8.

15. A lithium / sulfur accumulator comprising the cathode of claim 14.

Citation Information

Patent Citations

  • Positive electrode material of lithium-sulfur battery

    CN106450191A

  • Positive electrode material for flexible lithium-sulfur battery

    CN107221660A

  • Method of forming lamellar structure

    JP1979073886A

  • Centrifugal dehydrator

    JP1980086550A

  • Battery

    JP2006318759A